2003
DOI: 10.1001/archinte.163.13.1566
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Patients With Celiac Disease in a Population-Based Swedish Cohort

Abstract: The elevated mortality risk for all causes of death combined reflected, for the most part, disorders characterized by immune dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
215
4
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(244 citation statements)
references
References 70 publications
14
215
4
11
Order By: Relevance
“…This low global level of adherence to a GFD in individuals with CD is troubling given the known morbidity and mortality associated with long-term untreated symptomatic CD [7,11,28,29] and the lack of any other effective treatment. There are a variety of reasons why it is difficult to follow a GFD, including the fact that wheat-based food products are a major staple in the North American and European diet, and increasingly complex lifestyles have contributed to a greater reliance on packaged convenience foods and meals eaten away from home.…”
Section: Discussionmentioning
confidence: 99%
“…This low global level of adherence to a GFD in individuals with CD is troubling given the known morbidity and mortality associated with long-term untreated symptomatic CD [7,11,28,29] and the lack of any other effective treatment. There are a variety of reasons why it is difficult to follow a GFD, including the fact that wheat-based food products are a major staple in the North American and European diet, and increasingly complex lifestyles have contributed to a greater reliance on packaged convenience foods and meals eaten away from home.…”
Section: Discussionmentioning
confidence: 99%
“…12 Even more, CD was found to be associated with an 8-fold increased risk of death from liver cirrhosis. 13 Thus, CD needs to be excluded before a diagnosis of cryptogenic cirrhosis is considered. 14 CD should be suspected in those subjects with clinical risk factors for CD, such as a positive family history of gluten-sensitive enteropathy or dermatitis herpetiformis, and those who have the human leukocyte antigen DQ2 (HLA-DQ2) or HLA-DQ8 haplotypes, type 1 diabetes mellitus, premature osteoporosis, or osteomalacia.…”
Section: Liver Involvement In Celiac Diseasementioning
confidence: 99%
“…The interval between the diagnosis of CD and death was 4 year. PETERS et al (53) in a Swedish population reported that 828 patients with CD died between 1965-1994: non-Hodgkin lymphoma, cancer of the small intestine, autoimmune diseases as rheumatoid arthritis, diffuse disease of connective tissue, or allergic disorders (such as asthma), inflammatory bowel diseases, diabetes mellitus, disorders of immune deficiency, tuberculosis, pneumonia and nephritis. In summary, elevated mortality risk for all causes of death combined reflected, for the most part, disorders characterized by immune dysfunction.…”
Section: Mortality and Causes Of Deathmentioning
confidence: 99%